Occupational challenges facing chefs: the case of Cyprus - Kyprianou, George; Pavlou, Iphigenia; Zopiatis, Anastasios (My University, 2011)
Despite the euphoria caused by the enhanced popularity of culinary professions in Cyprus, stakeholders are skeptical of the numerous occupational challenges facing the profession. This research investigates the occupational challenges facing Chefs working in Cyprus. This article explores the perceptions of Chefs, in terms of importance and perceived level of satisfaction, on twenty issues shaping their occupation. Findings revealed that the five most important occupational issues are job security, monetary rewards and fringe benefits, appreciation by top management, training and development activities and the quality of working environment. In addition, the study examines whether significant differences exist between the Chefs' perceptions of occupational challenges and variables such as age, years of hospitality experience, type of hospitality establishment currently employed, educational background and job classification
Keywords: Chef professionals; HRM practices; Occupational challenges; Cyprus